“Composición química y transformación de la biomasa vegetal en abono orgánico”. - Mena Torres, Kevin Alexis (2023)
The present research was carried out in the experimental center "Sacha wiwa" located in the Guasaganda parish, Cotopaxi province, it lasted 120 days. In this way, the chemical composition and transformation of plant biomass into organic fertilizer was determined, using five treatments: T1 cocoa residues, T2 cutting grass residues, T3 grazing grass residues, and T4 forage residues. The variables evaluated were pH in the transformation process, temperature, electrical conductivity, volume of biomass, chemical composition of waste, and compost. Regarding the chemical composition of the compost obtained, the macronutrient content (N, P, K) of all the treatments was within the allowed range. The volume of biomass decreases as the composting process progresses. According to the economic analysis, the treatment with the highest profitability uses cocoa residues with a 20% profitability, followed by fodder grass treatment, which gets a profitability of 10%, the benefit/cost ratio B/N for the best treatment is 0.2, which indicates that for each dollar invested the researchers obtain 20 cents as a profit.